2008
DOI: 10.4141/cjas07147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lasalocid or monensin on in situ biohydrogenation of flaxseed and sunflower seed unsaturated fatty acids

Abstract: R. 2008. Effects of lasalocid or monensin on in situ biohydrogenation of flaxseed and sunflower seed unsaturated fatty acids. Can. J. Anim. Sci. 88: 335Á339. The objective of this study was to compare the effects of two ionophores, lasalocid and monensin (24 mg kg (1 dry matter), on in situ biohydrogenation of C 18:2 and C 18:3 from whole sunflower seed and flaxseed, respectively. There were no treatment effects on biohydrogenation of C 18:2 . Ionophore supplementation did not affect the lag time, but monensin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In in vivo studies of cows eating a diet supplemented with the ionophore monensin, the resultant milk fatty acid composition suggested a depressed ruminal BH: SFA including C16:0 decreased, and MUFA (specially the 18:1 trans isomers), PUFA, and CLA increased (Sauer et al, 1998;Odongo et al, 2007). Martineau et al (2008) observed a decrease in the rate of BH of C18:3 from linseed when the diet was supplemented with monensin. Because the antimicrobial activity of hops is similar to that of monensin, we expected to observe an inhibition of fatty acids BH resulting in higher UFA levels in milk; however, hops alone at the tested dose (2.9 g of HP/kg of DM) had no significant effect on the fatty acid profile of milk (experiment 1).…”
Section: Milk Fatty Acid Compositionmentioning
confidence: 99%
“…In in vivo studies of cows eating a diet supplemented with the ionophore monensin, the resultant milk fatty acid composition suggested a depressed ruminal BH: SFA including C16:0 decreased, and MUFA (specially the 18:1 trans isomers), PUFA, and CLA increased (Sauer et al, 1998;Odongo et al, 2007). Martineau et al (2008) observed a decrease in the rate of BH of C18:3 from linseed when the diet was supplemented with monensin. Because the antimicrobial activity of hops is similar to that of monensin, we expected to observe an inhibition of fatty acids BH resulting in higher UFA levels in milk; however, hops alone at the tested dose (2.9 g of HP/kg of DM) had no significant effect on the fatty acid profile of milk (experiment 1).…”
Section: Milk Fatty Acid Compositionmentioning
confidence: 99%
“…There are several activities of essential oils (Jayasena & Jo, 2013) as feed additives for livestock because they improve feed efficiency and animal productivity due to their antimicrobial, anti-inflammatory, antioxidant, and digestive modulatory effects on ruminal metabolism (Bakkali, Averbeck, Averbeck, & Idaomar, 2008;Benchaar et al, 2008). Their antimicrobial activity can decrease ruminal biohydrogenation and consequently increase the deposition of PUFA in meat (Martineau et al, 2008;Scollan et al, 2001).…”
Section: Introductionmentioning
confidence: 99%